EFFICACY, SAFETY, AND COST-EFFECTIVE ANALYSIS OF LOW-DOSE ETORICOXIB AND ADD-ON PARACETAMOL VERSUS THERAPEUTIC DOSE ETORICOXIB FOR PAIN IN PATIENTS AFTER TOOTH EXTRACTION: A RANDOMIZED INTERVENTIONAL DOUBLE-BLIND STUDY - SAROJ, KOTHARI; HARESH, BANSAL; YOGENDRA, PAHARIA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to study the efficacy, safety, and cost-effective analysis of low-dose etoricoxib and add-on paracetamol versus therapeutic dose etoricoxib in patients who experienced pain after tooth extraction. Methods: Patients were recruited and randomized to two study groups E1P and E2 on etoricoxib 30 mg and add-on paracetamol 500 mg 8 hourly and etoricoxib 60 mg once respectively for 3 days. The efficacy was assessed by visual analog scale, pain relief score, and global evaluation score. Patients were assessed at 0, 6, 24, 48, and 72 h. Safety was assessed by adverse drug reactions reported by the patients after 72 h. Cost-effective analysis was done by calculating the cost of treatment and the cost-effective ratio in both groups. Results: Eighty patients completed the study having 40 patients in each group. Mean pain intensity reduction, mean pain relief score, and global evaluation score all showed significantly better results (p<0.05) in Group E1P as compared to Group E2 at 6, 24, 48, and 72 h, respectively. No patient had reported any serious adverse drug reaction in both the groups; however, incidence of headache and fatigue was twice in the etoricoxib only treated group (n=4) than low-dose etoricoxib-treated group (n=2). The treatment cost of Group E1P was lesser than Group E2 and was also cost effective. Conclusion: Low-dose etoricoxib with add-on paracetamol is a better analgesic than therapeutic dose etoricoxib and is also found to be safer and cost effective.